The Decentralization and Religious Management Policy in Radical-Democratic Discourse : a Study of Religious Administration for Local Community Beliefs - Krisnaldo Triguswinri; Cynthia Hadita (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2022)
This article discusses the authority to carry out autonomous management of religious administrative policies that are denied by the central government of Indonesia where the regional government has no right to give recognition of a religion or belief embraced by the local community. The government only recognizes six administratively registered religions based on the population records. Those are Islam, Catholicism, Christianity, Buddhism, Hinduism, and Confucianism. The method used in this paper is normative juridical legal researhc. Whereas in the anthropological tradition of the local communities’ spiritual beliefs, Indonesia has 187 local beliefs with its unofficial number of trustees of 20 million people. Therefore, the religious beliefs embraced by the residents are ignored in public services and bureaucratic practices. Hence, the logical consequences that have implications for the adherents of local religious beliefs are the exclusion of basic rights as citizens, inequality before the law and government, discrimination in public services, restrictions on freedom of worship and tradition, being the recipients of racism, and forms of intolerance in society. This article will focus on conducting empirical-theoretical analysis of decentralization, religious administration policies, and relation to pluralist democratic discourse.